Navigating market volatility: risk and return insights from Indian mutual funds - Davinder Malhotra; Rahul Singh; L. Ramani (Cogent Economics & Finance, 2024)
This study evaluates Indian mutual funds using a variety of criteria, demonstrating a historical tendency of lower monthly returns and volatility when compared to benchmark indexes. This positive risk profile implies that it will appeal to investors who want stability. Despite COVID-19-induced market volatility, mutual funds persistently outperform benchmark indices in terms of average return per unit of risk, highlighting their potential as a dependable investment option for stability seekers. Furthermore, Indian mutual funds routinely beat benchmark indexes in risk-adjusted terms. Despite having a positive alpha, it lacked statistical significance, indicating a possible reliance on market volatility rather than managerial ability. Notably, while mutual fund managers demonstrated ability in asset selection, they lacked market timing abilities. The study also reveals that Indian mutual funds may demonstrate a considerably reduced downside risk in unfavorable market circumstances than comparable benchmarks. This study is valuable because it offers a thorough examination of Indian mutual funds, which may reveal a lot about their risk and return characteristics. The study demonstrates how, during difficult periods like the COVID-19 pandemic, these funds with reduced volatility and superior risk-adjusted returns consistently beat indexes. A stability-focused investor may learn about the benefits of Indian mutual funds for stock selection and the fault lines for market timing from this study. By increasing understanding of how mutual funds function in new markets, it provides investors and fund managers with a competitive edge over other investing professionals.
Keywords: 330; Indian mutual funds; market timing; Omega ratio; risk-adjusted returns; security selection; Sharpe ratio